ANALISIS GRADASI MATERI SARAF DALAM BUKU BELAJAR TASHRIF SISTEM 20 JAM KARYA KH. ACENG ZAKARIA - Amalia, Aam (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2017)
This research is motivated by the urgency of textbooks in the learning process. Books are one of the supporting factors for teaching success. With textbooks can help learners to achieve the expected learning goals. Therefore, this study intends to analyze a textbook that is often used, namely the Tashrif Learning System 20 Hours book by KH. Aceng Zakaria in terms of material gradations. With this research, it is expected that Arabic teachers can choose books that are good for learning. The type of research used is library research (library research) with the research object of the book Tashrif System 20 Hours of Work KH. Aceng Zakaria reviews analysis of material gradations. The results showed that the book Learning Tashrif System 20 Hours using grammatical gradation when viewed in terms of language. Whereas in terms of type, the Learning Tashrif System 20 Hours book uses straight gradation. As for the criteria, the pattern of compiling the book Learning Tashrif System 20 Hours starts from the general to the special one.